Allogeneic Transplantation for Chronic Lymphocytic Leukemia - Laurenti, Luca (Università Cattolica del Sacro Cuore, 2010)
Even if Chronic lymphocytic leukemia (CLL) often has an indolent behavior with good responsiveness to cytoreductive treatment, about 20% of the patients, so called “poor-risk” patients, show an aggressive course and die within a few years despite early intensive therapies. Criteria for poor-risk disease according to the European Bone Marrow Transplantation (EBMT) CLL Transplant Consensus are: purine analogue refractoriness, early relapse after purine analogue combination therapy, CLL with p53 lesion requiring treatment. Allogeneic transplant has potential curative role in CLL, however burden with very high transplant related mortality (TRM) rates of 38–50%. A major advance in reducing the short-term morbidity and mortality of allogeneic stem cell transplantation (SCT) has been the introduction of non-myeloablative or reduced intensity conditioning (RIC) regimens to allow engraftment of allogeneic stem cells. There is no doubt that the crucial therapeutic principle of allo-SCT in CLL is graft versus leukemia (GVL) activity. The major complications of allogeneic SCT in CLL are: chronic graft-versus-host-disease (GVHD) affecting quality of life, high graft rejection and infection rates correlated with preexisting immunosuppression. Disease relapse remains the major cause of failure after RIC allo-HCT in CLL patients. Sensitive minimal residual disease (MRD) quantification has strong prognostic impact after transplant.